2014
DOI: 10.1111/nan.12057
|View full text |Cite
|
Sign up to set email alerts
|

Progressive myoclonus epilepsy: extraneuronal brown pigment deposition and system neurodegeneration in the brains of Japanese patients with novel SCARB2 mutations

Abstract: The frameshift mutation detected in the patient with late-onset disease is a hitherto undescribed, unique type of SCARB2 gene mutation. The present two patients are the first reported to have clearly demonstrated both extraneuronal brown pigment deposition and system neurodegeneration as neuropathological features of PME with SCARB2 mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Widespread deposition of abnormal, extraneuronal brown pigment in the brain, with no neuronal loss or significant gliosis, has been reported in AMRF patients (Andermann et al, 1986;Badhwar et al, 2004), and more recently in two patients with PME without renal failure associated with SCARB2 mutations (Fu et al, 2014). Based on the staining characteristics, it has been suggested that the pigment consists of lipofuscin-like oxidized lipid or proteolipid (Badhwar et al, 2004).…”
Section: Histologymentioning
confidence: 98%
See 3 more Smart Citations
“…Widespread deposition of abnormal, extraneuronal brown pigment in the brain, with no neuronal loss or significant gliosis, has been reported in AMRF patients (Andermann et al, 1986;Badhwar et al, 2004), and more recently in two patients with PME without renal failure associated with SCARB2 mutations (Fu et al, 2014). Based on the staining characteristics, it has been suggested that the pigment consists of lipofuscin-like oxidized lipid or proteolipid (Badhwar et al, 2004).…”
Section: Histologymentioning
confidence: 98%
“…Since this initial report, other cases have been reported and the clinical features of PME without renal failure associated with SCARB2 have been described (Rubboli et al ., ; Guerrero‐López et al ., ; Higashiyama et al ., ; Fu et al ., ; Zeigler et al ., ). Features seen in these patients included a variable severity of epilepsy: from uncontrolled seizures or status epilepticus with prominent photosensitivity in patients with adolescent onset, to infrequent or no major seizures in patients with a more delayed onset (Rubboli et al ., ), late onset in adulthood (Higashiyama et al ., ; Fu et al ., ), and the occurrence of dementia (Fu et al ., ). These findings suggest that SCARB2 mutations in patients with PME without renal complications might not be rare and that SCARB2 gene mutations should therefore be evaluated even in the absence of renal involvement.…”
Section: Clinical Features Of Action Myoclonus Renal Failurementioning
confidence: 98%
See 2 more Smart Citations
“…LIMP-2-deficient (LIMP-2 −/− ) mice (4) are a valid disease model for AMRF. To date, several SCARB2 mutations have been identified in AMRF, as well as in some PME cases (5,6). AMRF/PME mutants mislocalize to the endoplasmic reticulum (ER) and fail to transport GC to lysosomes (7,8).…”
mentioning
confidence: 99%